The role of lactoferrin in bone remodeling: evaluation of its potential in targeted delivery and treatment of metabolic bone diseases and orthopedic conditions - Tian, Miao; Han, Ying-bo; Yang, Gui-yun; Li, Jin-long; Shi, Chang-sai; Tian, Dan (Frontiers in Endocrinology, 2023)
Lactoferrin (Lf) is a multifunctional protein that is synthesized endogenously and has various biological roles including immunological regulation, antibacterial, antiviral, and anticancer properties. Recently, research has uncovered Lf's critical functions in bone remodeling, where it regulates the function of osteoblasts, chondrocytes, osteoclasts, and mesenchymal stem cells. The signaling pathways involved in Lf'ssignaling in osteoblasts include (low density lipoprotein receptor-related protein -1 (LRP-1), transforming growth factor  (TGFβ), and inslin-like growth factor -1 (IGF-1), which activate downstream pathways such as ERK, PI3K/Akt, and NF-κB. These pathways collectively stimulate osteoblast proliferation, differentiation, and mineralization while inhibiting osteoclast differentiation and activity.Additionally, Lf's inhibitory effect on nuclear factor kappa B (NF-κB) suppresses the formation and activity of osteoclasts directly. Lf also promotes chondroprogenitor proliferation and differentiation to chondrocytes by activating the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) and phosphoinositide 3kinase/protein kinase B(PI3K/Akt)signaling pathways while inhibiting the expression of matrix-degrading enzymes through the suppression of the NF-κB pathway. Lf's ability to stimulate osteoblast and chondrocyte activity and inhibit osteoclast function accelerates fracture repair, as demonstrated by its effectiveness in animal models of critical-sized long bone defects. Moreover, studies have indicated that Lf can rescue dysregulated bone remodeling in osteoporotic conditions by stimulating bone formation and suppressing bone resorption. These beneficial effects of Lf on bone health have led to its exploration in nutraceutical and pharmaceutical applications. However, due to the large size of Lf, small bioactive peptides are preferred for pharmaceutical applications. These peptides have been shown to promote bone fracture repair and reverse osteoporosis in animal studies, indicating their potential as therapeutic agents for bone-related diseases. Nonetheless, the active concentration of Lf in serum may not be sufficient at the site requiring bone regeneration, necessitating the development of various delivery strategies to enhance Lf's bioavailability and target its active concentration to the site requiring bone regeneration. This review provides a critical discussion of the issues mentioned above, providing insight into the roles of Lf in bone remodeling and the potential use of Lf as a therapeutic target for bone disorders.